Co archeolodzy robią nocami? Działalność wydawnicza jednostki naukowej na przykładzie Instytutu Archeologii Uniwersytetu Wrocławskiego - Sawicka, Natalia (2023)
This text concerns the history of the publishing activities of the Institute of Archeology of the University of Wrocław. So far, no attempt has been made to record the publication activity of this scientific unit, which constitutes a significant contribution to the development of Polish archeology, especially since it concerns a research unit established from scratch in the so-called “recovered territories”. The period under study covers the beginnings of the activity of the current Institute of Archeology of the University of Wrocław in the years after World War II until modern times. The text is supplemented with a full bibliography of publications.
Keywords: publishing; scientific periodicals; editing; science studies